The Bacterial Nucleoid: Nature, Dynamics and Sister Segregation - Kleckner, Nancy (Curr Opin Microbiol, 2014)
Recent studies reveal that the bacterial nucleoid has a defined, self-adherent shape and an underlying longitudinal organization and comprises a viscoelastic matrix. Within this shape, mobility is enhanced by ATP-dependent processes and individual loci can undergo ballistic off-equilibrium movements. In E.coli, two global dynamic nucleoid behaviors emerge pointing to nucleoid-wide accumulation and relief of internal stress. Sister segregation begins with local splitting of individual loci, which is delayed at origin, terminus and specialized interstitial snap regions. Globally, as studied in several systems, segregation is a multi-step process in which internal nucleoid state plays critical roles that involve both compaction and expansion. The origin and terminus regions undergo specialized programs partially driven by complex ATP burning mechanisms such as a ParAB Brownian ratchet and a septum-associated FtsK motor. These recent findings reveal strong, direct parallels among events in different systems and between bacterial nucleoids and mammalian chromosomes with respect to physical properties, internal organization and dynamic behaviors.